2015
DOI: 10.1002/2014jc010415
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic parameters in the northern South China Sea in relation to phytoplankton community structure

Abstract: Many recent models for retrieval of primary production in the sea from ocean-color data are temperature based. But previous studies in low latitudes have shown that models that include phytoplankton community structure can have improved predictive capability. In this study, we measured photosynthetic parameters from photosynthesis-irradiance (P-E) experiments, phytoplankton absorption coefficients, and phytoplankton community structure derived from algal pigments during four cruises in the northern South China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 93 publications
(168 reference statements)
0
32
0
Order By: Relevance
“…Over the past three decades, considerable efforts have been made to establish a global database of P-I parameters ( [2,31,33,86]; this study) and to decipher their empirical relationships with physico-chemical and optical properties to enable prediction of photosynthetic parameters on regional and global scales [38,40,41,[105][106][107][108]. The observed relationships between physico-chemical conditions and P-I parameters in the present study confirmed earlier observations that temperature may be a good predictor of the assimilation number (P B m ), especially in coastal regions and temperate oceanic regions where temperature and associated water column stability dictates seasonal changes in the taxonomic and size structure of phytoplankton communities [40,86,109].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past three decades, considerable efforts have been made to establish a global database of P-I parameters ( [2,31,33,86]; this study) and to decipher their empirical relationships with physico-chemical and optical properties to enable prediction of photosynthetic parameters on regional and global scales [38,40,41,[105][106][107][108]. The observed relationships between physico-chemical conditions and P-I parameters in the present study confirmed earlier observations that temperature may be a good predictor of the assimilation number (P B m ), especially in coastal regions and temperate oceanic regions where temperature and associated water column stability dictates seasonal changes in the taxonomic and size structure of phytoplankton communities [40,86,109].…”
Section: Discussionmentioning
confidence: 99%
“…Both taxon-specific and size-specific differences in P B m and α B have been reported in both culture and field studies (Bouman et al, 2005;Côté andPlatt, 1983, 1984;Huot et al, 2013;Xie et al, 2015). As new remote-sensing algorithms are now starting to yield information on the size and taxonomic structure of phytoplankton, it would be useful to derive additional information on the P-E response of key phytoplankton taxa and size classes, especially those implicated as playing key roles in ocean biogeochemical cycles (LeQuéré et al, 2005;Nair et al, 2008;Bracher et al, 2017).…”
Section: Discussionmentioning
confidence: 92%
“…We have included in the database quality flags indicating whether a correction factor for the spectrum of the lamp was applied to obtain a readily intercomparable broadband (white light) value (e.g. Kyewalyanga et al, 1997;Xie et al, 2015). This broad-band α B combined with information on the shape of the phytoplankton absorption spectrum has been shown to provide an accurate estimate of the photosynthetic action spectrum α B (λ).…”
Section: Experimental Conditionsmentioning
confidence: 99%
“…At the base of the NRL, F e _DIN was (1.1 ± 0.1) × 10 −1 mmol N m −2 d −1 , much higher than that in the NDL. Here the integrated PP was 3.33 mmol C m −2 d −1 (Xie et al, ). The difference in EP between 75 m and 47 m was 1.24 ± 0.48 mmol C m −2 d −1 , requiring 0.19 ± 0.07 mmol N m −2 d −1 of DIN, consistent with the estimated new nutrients sourced from depth, suggesting that diapycnal nutrient fluxes were sufficient to sustain EP from the NRL.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, continuous profiling sensor measurements of NO 3 ‐ (ISUS, Satlantic) and DO were conducted. Detailed analytical methods are introduced in the supporting information (Bourgault et al, ; Cao & Dai, ; Dai et al, ; Han et al, ; Johnson et al, ; Ma et al, ; Xie et al, ; Zhang, ; Zhou et al, ; Zhu et al, ).…”
Section: Methodsmentioning
confidence: 99%